Propuesta para el uso, reúso y reciclaje del agua residual en una vivienda en la localidad de Pinto Recodo - Pinedo Gonzalez, Alin. (2013)
About 40% of potable water consumption in a home is used to flush the toilet, toilet called in our country, and a similar percentage in bathing, so we can assume that 80% of the daily consumption we are pulling the drain, without realize the social and environmental damage we are causing. Seeing this actually posed the question, "How to build a house maximizing the water through use, reuse and recycling, without damaging the environment, using a system that achieves minimize water indiscriminate spending on activities and tasks that require such, it is designed for a target of much importance, which plans to propase specifications to reduce potable water consumption through the reuse of domestic wastewater in a home, secure sanitary conditions, and designing a computer allow greywater reuse these, in the first instance redirecting bathing water used to feed the toilets, and then to drain. This allows up to 40% of potable water. The team designed and constructed to be suitable for new construction, and will fit in most bathrooms and sometimes built cheaply and allowing any plumber can install. The methodology specifies that wastewater can be mainly divided into domestic sewage (from toilets with feces) and gray water (from washing in general as: kitchens, sinks, showers, containing detergents, remains food, organic matter and other pollutants). Therefore it is proposed to implement a system of domestic wastewater reuse, where the water generated from showers, sinks and dishwashers serve to supply the toilet tank and the water generated from toilets is transported to the sewage system, all of the above safe and controlled manner. The water used for showers, sinks, dishwashers and washing machines is piped into the gray water tank, located in the most suitable place in the house. When we actívate the discharge device of toilet tanks and discharged it, the pump incorporates the storage tank drives greywater to reload the toilet tanks. Greywater is conducted, and then move to an underground irrigation system in the garden area, with perforated pipes that are buried in the ground to a certain depth creating a constant drip. When implementing such systems must meet the operational and maintenance presented to ensure sustainability and shortterm system does not generate majar problems. The results of the characterization of treated wastewater to secondary treatment level, to conclude its total technical feasibility for reuse in non-potable uses investigated, since the addition of tertiary treatment recommended in the proposed rule. The application of the methodology Hernández Muñoz environmental impact assessment, has been very effective in defining the requirements for water quality to be reused and tertiary treatments required.